2015
DOI: 10.3390/met5042093
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Structural Features in Metallic Glass via Synchrotron Radiation Experiments Combined with Simulations

Abstract: Abstract:Revealing the essential structural features of metallic glasses (MGs) will enhance the understanding of glass-forming mechanisms. In this work, a feasible scheme is provided where we performed the state-of-the-art synchrotron-radiation based experiments combined with simulations to investigate the microstructures of ZrCu amorphous compositions. It is revealed that in order to stabilize the amorphous state and optimize the topological and chemical distribution, besides the icosahedral or icosahedral-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 56 publications
0
18
0
Order By: Relevance
“…Take Figure 3b for example, the popular Zr-centered VCs are 12-CN ones (<0,2,8,2> and <0,3,6,3>) and 13-CN ones (<0,1,10,2> and <0,3,6,4>), while none of them has a fraction higher than 16%. This indicates that various clusters co-existing to form the microstructure is the intrinsic structural feature in glassy alloys [39], and icosahedral clusters are the preferred but not the only clusters favored in the glassy structure, because only stacking icosahedral clusters can not fill space completely [39]. In addition, the Zr-centered icosahedral-like VCs in both samples have high weights, while fractions of the Cu-centered icosahedral-like counterparts are relatively small, let alone the Al-centered ones.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Take Figure 3b for example, the popular Zr-centered VCs are 12-CN ones (<0,2,8,2> and <0,3,6,3>) and 13-CN ones (<0,1,10,2> and <0,3,6,4>), while none of them has a fraction higher than 16%. This indicates that various clusters co-existing to form the microstructure is the intrinsic structural feature in glassy alloys [39], and icosahedral clusters are the preferred but not the only clusters favored in the glassy structure, because only stacking icosahedral clusters can not fill space completely [39]. In addition, the Zr-centered icosahedral-like VCs in both samples have high weights, while fractions of the Cu-centered icosahedral-like counterparts are relatively small, let alone the Al-centered ones.…”
Section: Resultsmentioning
confidence: 94%
“…Therefore, more icosahedral-like local structures exist in the Cu46Zr42Al7Y5 quarternary MG. In previous work, it has been revealed that icosahedral local structures contribute to the formation of MGs [46,47], because stacking clusters with abundant five-fold point symmetrical features such as icosahedra can result in the exclusion of structural periodicity, which is required in crystals [39]. In this sense, increase of the icosahedral-like clusters leads to stabilization of the amorphous microstructure in the Cu46Zr42Al7Y5 alloy, greatly enhancing the GFA.…”
Section: Resultsmentioning
confidence: 97%
“…The structure of metallic glass is further discussed by Guo et al, particularly how synchrotron radiation [16] and combined simulations [17] are employed to determine icosahedral and icosahedral-like clusters. Both techniques, diffraction and absorption spectroscopy, EXAFS, are used to index Voronoi clusters in a tessellation.…”
Section: Metallic Glass and Disordered Crystalsmentioning
confidence: 99%
“…Various studies have been reported which shed light on different aspects of their manufacturing [12] [25] [26] and microstructural development [27] [28] [29] [30]. These include observations under abrasion corrected transmission electron microscopy [31], synchrotron light [32] [33] [34] [35] and in-situ studies [36] [37] [38] [39] but none have been made on the detailed use of more recent and advanced electron back scattered diffraction. Only three notable studies have been recently reported [40] [41] [42] but they are only qualitative and are limited by mere generalised phase identification.…”
Section: Introductionmentioning
confidence: 99%